Cambodia Economic Update, April 2018 : Recent Economic Developments and Outlook - World Bank Group (World Bank, Phnom Penh, 2018)
While the economy continues to expand rapidly in Cambodia, real GDP growth eased to 6.8percent in 2017 from 7 percent in 2016. Cambodia therefore bucked the regional trend, asmost developing countries in East Asia experienced a growth acceleration in 2017. Followingsome moderation during the first half of 2017, textile and apparel exports rebounded. Thetourism and agriculture sectors experienced initial recovery in the last few years after facinggradual moderation. Growth is projected to remain robust, expanding at 6.9 percent in 2018.Downside risks to the outlook include erosion of export competitiveness due to rapidly risingreal wages, a buildup of vulnerabilities from a prolonged real estate and construction boom,potential election-related uncertainty, and periodic jolts to the international trade order inthe form of protectionism and escalating trade disputes. This edition of Cambodia economic update is focusing on findings of future jobs in Cambodia.